A framework to incorporate spatiotemporal variability of rainfall extremes in summer monsoon declaration in India. (1st September 2022) - Mishra, Vimal; Tiwari, Amar Deep; Kumar, Rohini
Abstract: The Indian summer monsoon rainfall is a lifeline for agricultural activities and the socio-economic development of more than 1 billion people. All-India averaged summer monsoon rainfall has about 10% variability from its long-term mean. A departure of all-India averaged precipitation within ±10% is declared a normal summer monsoon. Using the long-term (1901–2021) gridded rainfall observations, we highlight the limitations in the current approach to the declaration of the normal summer monsoon, which ignores the role of spatiotemporal variability of rainfall. Dry and wet extremes within the same monsoon season can lead to a normal monsoon. Moreover, different parts of the country face drought and wet extremes, while the summer monsoon can be declared normal. Considering the profound implications of dry and wet extremes on agricultural activities, we propose a novel framework to account for the rainfall variability in the declaration of the summer monsoon. The proposed framework accounts for the temporal variability through a combined severity coverage index, while spatial variability using a clustering approach. Based on the existing framework, we find that 84 years were declared normal in the last 121 years (1901–1921). However, 13 years (out of 84) were not normal based on the new framework due to dry and wet extremes occurring at different times and in different regions. The new framework of summer monsoon declaration can account for the occurrence of extremes and their implications for agriculture and water management.